2023
DOI: 10.15376/biores.18.1.1384-1397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the factors affecting opening-closing performance of wooden cabinet doors

Abstract: This study determined the deflection performance of wooden cabinet doors during opening and closing by using different material types, opening-closing angle, and load force. The independent variables consisted of material type, opening-closing angle, and load force, and the dependent variable was determined as deflection value. Medium density fiberboard (MDF) and particleboard (PB), both melamine faced, were used as two different material types. Opening and closing angles and directions of forces were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Supporting this result, Sert (2018) carried out mechanical experiments on 80 cm kitchen cabinets made of MDF and PB materials with two hinges and found that the loadbearing value of cabinets made of MDF material was higher. In addition, Erdinler et al (2023) determined the bending performance of the covers during opening-closing using different material types and opening-closing angle load and found that the deformation value of MDF covers was lower than PB. One of the results of the lid tests is that the test ends when the hinge breaks or the hinge fails to perform its opening-closing function and the lid falls.…”
Section: Deflection Values and Damage Symptoms For Kitchen Cabinet Do...mentioning
confidence: 99%
“…Supporting this result, Sert (2018) carried out mechanical experiments on 80 cm kitchen cabinets made of MDF and PB materials with two hinges and found that the loadbearing value of cabinets made of MDF material was higher. In addition, Erdinler et al (2023) determined the bending performance of the covers during opening-closing using different material types and opening-closing angle load and found that the deformation value of MDF covers was lower than PB. One of the results of the lid tests is that the test ends when the hinge breaks or the hinge fails to perform its opening-closing function and the lid falls.…”
Section: Deflection Values and Damage Symptoms For Kitchen Cabinet Do...mentioning
confidence: 99%